Development Of Interactive Learning Media With Powerpoint To Increase Students’ Motivation To Learn Mathematics - Rahmadani, Suci; Mesiono; Rakhmawati, Fibri (Yana Research, 2022)
This study aims to develop interactive learning media with powerpoint to increase students' motivation to learn mathematics in class VII SMP N 5 One Roof Halongonan. This study also aims to determine the process of media development, feasibility, and practicality of the developed media. The teaching material presented by the researcher is statistical data presentation for class VII SMP N 5 One Roof Halongonan. The subjects in this research are seventh grade students of SMP N 5 One Roof Halongonan.This type of research is research and development that produces a product in a certain area of ​​ability, which is accompanied by certain by-products and has the effectiveness of a product. This research refers to the development model according to Borg and Gall, development research is a process used to develop and validate educational products. The process stages in this research and development form a consistent cycle to produce a certain product according to needs through certain steps including designing the initial product, testing the initial product to find various weaknesses, improving the product, testing the product that has been repaired, product improvement again until a good final product is obtained.The learning media developed in this research is declared valid, based on the percentage score of eligibility by media experts, which is 100% and by material experts, which is 87.5% with a feasible category. From the teacher response questionnaire data, it can also be seen that the teacher assesses the learning media as being very practical with reaching a percentage of 91%. And according to student responses the learning media developed is included in the very practical criteria with a percentage of 92%. The developed learning media has met the very practical criteria.